Quantitative analysis of miRNAs using SplintR ligase-mediated ligation of complementary-pairing probes enhanced by RNase H (SPLICER)-qPCR - Xinshu Qin; Xingyu Wang; Ke Xu; Yi Zhang; Hongye Tian; Yinglei Li; Bangran Qi; Xingbin Yang (Elsevier, 2023)
Here, a method using SplintR ligase-mediated ligation of complementary-pairing probes enhanced by RNase H (SPLICER) for miRNAs quantification was established. The strategy has two steps: (1) ligation of two DNA probes specifically hybridize to target miRNA and (2) qPCR amplifying the ligated probe. The miRNA-binding regions of the probes are stem-looped, a motif significantly reduces nonspecific ligation at high ligation temperature (65°C). The ends of the probes are designed complementary to form a paired probe, facilitating the recognition of target miRNAs with low concentrations. RNase H proved to be able to stabilize the heteroduplex formed by the probe and target miRNA, contributing to enhanced sensitivity (limit of detection = 60 copies). High specificity (discriminating homology miRNAs differing only one nucleotide), wide dynamic range (seven orders of magnitude) and ability to accurately detect plant miRNAs (immune to hindrance of 2'-O-methyl moiety) enable SPLICER comparable with the commercially available TaqMan and miRCURY assays. SYBR green I, rather than expensive hydrolysis or locked nucleic acid probes indispensable to TaqMan and miRCURY assays, is adequate for SPLICER. The method was efficient (<1 h), economical ($7 per sample), and robust (able to detect xeno-miRNAs in mammalian bodies), making it a powerful tool for molecular diagnosis and corresponding therapy.